Islam di Medan Estate: Studi Kegiatan Keagamaan Organisasi Muhammadiyah Sejak Tahun 2003-2023 - Nasution, Abdul Gani Jamora; Pane, Fizri Aspika Putri; Lubis, Iga Naila Aulia Br; Kharisma, Mutiara Indah; Khairani, Yesa Dwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out what activities the Muhammadiyah organization does in Medan Estate. This study used qualitative research methods. The data collection technique uses the interview method. This research discusses the development and activities of the Muhammadiyah organization in Medan Estate. Muhammadiyah means followers of the prophet Muhammad. Muhammadiyah is the largest organization in Indonesia. The results of this research show that the Muhammadiyah organization in Medan Estate is developing quite well. There are also many and increasing members or followers of Muhammadiyah. There are many useful Muhammadiyah organizational activities carried out by the Muhammadiyah community in Medan Estate.